Research and development of a web geospatial query interface - Tzovla, Georgia (The University of Edinburgh, 2014)
The multitude of spatial data in combination with the rapid growth of Internet technology set Human Computer Interaction (HCI) methods as a core component of the online geospatial development process. Considering the increasing number of people that can access online GIS services, a user-friendly and intuitive interface that allows an easy and effective interaction is essential. This research paper aims to examine and apply Human Computer Interaction methods in GIS, for the implementation of a geospatial query interface of the Unlock Places service. Unlock Places is a web service implemented by EDINA that combines spatial data from different data sources but does not provide an interface to give the opportunity to non-experts to interact with the service and exploit its possibilities. Following HCI methods, including user-centred design approaches, the elements that influence the user interface design are presented in this study. Specifically, the potential users of the service are identified and a survey is used to define their requirements in terms of spatial information. Based on the survey results, personas that capture users’ needs are created and lead the design process. Then, the final interface is been structured through a continuous refinement of prototype designs. The implementation is based on JavaScript and especially Leaflet, which is an opensource library for interactive maps. Its functional capabilities are examined and used in combination with Unlock Places’ API specifications for the implementation of the interactive interface. Finally, to evaluate the effectiveness of the interface, usability testing techniques are used. Specifically, ten participants are invited to complete specific tasks on the implemented web page and their overall performance and interaction is recorded. The results show that users appreciate the simplicity and clarity of the available functionalities on the map and they find the service useful and easy to learn. Further improvements and limitations of the study are also included.
Keywords: MSc Geographical Information Science; GIS; Human Computer Interaction; User-centred design; Geospatial map service; User Interface; User experience; Usability